2000
DOI: 10.1084/jem.192.9.1281
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Self-Renewal Division of Hematopoietic Stem Cells

Abstract: Little is known about how hematopoietic stem cells (HSCs) self-renew. We studied the regeneration of HSCs in culture. Effects of various cytokines on cell division of CD34−/low c-Kit+Sca-1+ lineage marker–negative (CD34−KSL) bone marrow cells of the mouse were first evaluated in serum-free single cell culture. We then performed a competitive repopulation assay on divided cells to ask if such cell division involved self-renewal of HSCs.In the presence of stem cell factor (SCF), thrombopoietin (TPO) induced a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
209
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(227 citation statements)
references
References 36 publications
15
209
0
3
Order By: Relevance
“…Rac1 À/À HSPCs reportedly responded to SCF with reduced in vitro cell growth, [16] but showed a normal proliferative response to combinations of multiple cytokines [15]. The CD34 À KSL cell fraction used in this study represents a highly purified HSC population in which SCF alone does not support sufficient cell growth [25]. We therefore used multiple cytokines to study the proliferative responses of these cells [22,25].…”
Section: Functional Analyses Of Hscs Rendered Defective In Wave2 Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 À/À HSPCs reportedly responded to SCF with reduced in vitro cell growth, [16] but showed a normal proliferative response to combinations of multiple cytokines [15]. The CD34 À KSL cell fraction used in this study represents a highly purified HSC population in which SCF alone does not support sufficient cell growth [25]. We therefore used multiple cytokines to study the proliferative responses of these cells [22,25].…”
Section: Functional Analyses Of Hscs Rendered Defective In Wave2 Exprmentioning
confidence: 99%
“…The CD34 À KSL cell fraction used in this study represents a highly purified HSC population in which SCF alone does not support sufficient cell growth [25]. We therefore used multiple cytokines to study the proliferative responses of these cells [22,25]. As shown in Figure 3A, CD34 À KSL HSCs transduced with either control virus (top) or WAVE2 shRNA virus (bottom) yielded substantial numbers of myeloid colonies (>1 mm diameter), most of which showed GFP fluorescence (>85% transduction efficiency).…”
Section: Functional Analyses Of Hscs Rendered Defective In Wave2 Exprmentioning
confidence: 99%
“…[12][13][14] Recently, some evidence for the occurrence of asymmetric cell division of mouse HSCs was provided in a transplantation model. 15,16 In studies using human HSC-enriched cells of the CD34 ϩ CD38 Ϫ fraction we and others have shown that CD34 ϩ CD38 Ϫ cells are heterogeneous in respect to their function and their proliferation kinetics (ie, the proliferation rate of more primitive cells is lower than that of committed ones). [17][18][19] Furthermore, it was observed that approximately 30% of the CD34 ϩ CD38 Ϫ cells gave rise to daughter cells with heterogeneous proliferation kinetics, perhaps the result of an asymmetric cell division.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, factors in the IL-6 family maintain the pluripotentiality of mouse embryonic stem (ES) cells through activation of the STAT3 pathway [22][23][24][25][26][27]. In addition, growth of human primordial germ cells requires LIF, SCF, and bFGF [28], whereas SCF, FLT3L, TPO, and IL-6 synergize with each other to promote expansion of hematopoietic progenitors [29][30][31][32][33][34][35][36][37]. In this report, we demonstrate that hESCs can be maintained in bFGF or bFGF in combination with other growth factors in a serum replacement nonconditioned medium (SR medium).…”
Section: Introductionmentioning
confidence: 99%